Análise Física e Química de Solos Formados a Partir de Resíduos de Serraria e Solos Originais de Tailândia-PA - Cometti, José Luís Said (Museu Paraense Emílio Goeldi, 2023)
The municipality of Tailândia, located in the mesoregion of northeast Pará, stands out for its industrial lumber activity, which represents 8% of the State's production (IBGE, 2000). The waste from this activity reaches more than 50%, with significant generation of residues (IMAZON, 1998), generally disposed of in the open air, causing serious socio-environmental problems. In an attempt to reduce these impacts, the veneer and plywood company Tailâminas has been using veneer waste as organic material to cover its plantations of Paricá (Schízolobium amazonicum) and Pupunha (Bactrís Gasipaes HBK) for five years. This work aimed to verify the probable modifications of the soil in these crops with and without cover, comparing them. Samples were collected and the profiles of the Paricá and Pupunha plantations were described, following the methodology of Lemos and Santos (1997). The physical properties analyzed were: bulk density, soil density, water retention at low and high pressures (0.06 - 1500Pa), and total porosity. The chemical properties analyzed were: Ca, Mg, P, Na, K, N, C, M.O., pH in water and KCI(EMBRAPA,1997). The results show that the density of the soils in the profiles where there was addition of the residues is lower (Paricál = 1.19 and Paricá = 1.51g1Kg), making them more porous, which according to VIElRA (1988), represents a better structured soil, facilitates the infiltration of water and favors good plant development. The amount of M.O. was greater in the superficial horizons and in the profiles with residues (Paricá1 = 20.84 and Paricá2 = 9.03g1Kg), as well as the content of nutrients, such as P (Paricá1 = 5 and Paricá2 = 2mgldm3 ) and Ca+Mg (Pupunhal = 3.6 and Pupunha2 = 2.Ocmoljdm3). It can be verified that the addition of wood residues contributed to the improvement of the physical and chemical properties of the soil, also visible in the good development of the reforestation cultures of Paricá and Pupunha, The reuse of these residues as organic fertilizer can be an alternative to strengthen agriculture in our state and promote better local quality of life.